Parental Involvement in Promoting Academic Motivation among Third Grade Students at Nahdlatul Ulama Madrasah Ibtidaiyah, Balikpapan - Rohmaningsih, Yuni; Baihaqi, Mohammad (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2024)
Human behavior is the main goal of education, and the role of parents is crucial in motivating children's learning. To support their children, parents can provide attention, gifts, and rewards. This research aims to find out how parents can motivate their children's learning process, using a qualitative descriptive methodology with interviews and observations. The results show that parents have fulfilled their roles as teachers for their children, although sometimes not perfectly. They motivate their children with praise and guidance, and provide learning facilities such as books and writing tools. However, they also face challenges such as knowledge gaps, financial constraints, and children's traits that can hinder learning, such as laziness and lack of focus.